Answer:x = 2
Explanation:
Simplifying
3(x + -4) = 2(-2x + 1)
Reorder the terms:
3(-4 + x) = 2(-2x + 1)
(-4 * 3 + x * 3) = 2(-2x + 1)
(-12 + 3x) = 2(-2x + 1)
Reorder the terms:
-12 + 3x = 2(1 + -2x)
-12 + 3x = (1 * 2 + -2x * 2)
-12 + 3x = (2 + -4x)
Solving
-12 + 3x = 2 + -4x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '4x' to each side of the equation.
-12 + 3x + 4x = 2 + -4x + 4x
Combine like terms: 3x + 4x = 7x
-12 + 7x = 2 + -4x + 4x
Combine like terms: -4x + 4x = 0
-12 + 7x = 2 + 0
-12 + 7x = 2
Add '12' to each side of the equation.
-12 + 12 + 7x = 2 + 12
Combine like terms: -12 + 12 = 0
0 + 7x = 2 + 12
7x = 2 + 12
Combine like terms: 2 + 12 = 14
7x = 14
Divide each side by '7'.
x = 2
Simplifying
x = 2